The Illusion of Women’s Substantive Representation: Normative Vacuum in Committee Assignments of the Central Java Provincial DPRD - Ristina Yudhanti; Krisna Eka; Ani Purwanti; Edvardas Juchnevicius; Rengga Kusuma Putra (Vifada Assumption Journal of Law, 2026)
Purpose: This study examines how the normative vacuum in the Rules of Procedure of the Central Java Provincial DPRD undermines women’s substantive representation within committee assignments and formulates institutional reforms to address the resulting pattern of gendered portfolios and glass walls. Research Design and Methodology: This normative legal research employs a statutory approach, a conceptual approach grounded in Feminist Jurisprudence and institutional sociology, and a case approach to analyze the internal legal structure governing the Parliamentary Completeness Apparatus (AKD). Findings and Discussion: The findings show that the absence of binding rules on proportional distribution leaves committee assignments to factional discretion, producing gendered portfolios through the concentration of women in welfare-related committees and reinforcing glass walls that limit their access to strategic budgetary and infrastructural bodies. This condition demonstrates that women’s electoral presence in the DPRD has not yet been translated into substantive representation within the AKD. Implications: The study therefore recommends institutional engineering through binding amendments to the Rules of Procedure, including cross-commission distribution, mandatory women’s representation in the Budget Committee, and proportional leadership arrangements within the AKD in line with Constitutional Court Decision Number 169/PUU-XXII/2024.